2020
DOI: 10.1101/2020.06.18.20133660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2-specific antibody detection for sero-epidemiology: a multiplex analysis approach accounting for accurate seroprevalence

Abstract: Background The COVID-19 pandemic demands detailed understanding of the kinetics of antibody production induced by infection with SARS-CoV-2. We aimed to develop a high throughput multiplex assay to detect antibodies to SARS-CoV-2 to assess immunity to the virus in the general population. Methods Spike protein subunits S1 and RBD, and Nucleoprotein were coupled to distinct microspheres. Sera collected before the emergence of SARS-CoV-2 (N=224), and of non-SARS-CoV-2 influenza-like illness (N=184), and laborato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…In our comparison to commercially available IVD tests, we classified fewer samples as false negative using our MultiCoV-Ab assay. For 10% of all infected samples, we could not detect a SARS-CoV-2 specific immune response, which is in line with previous findings 3,15,16 . Those non-responders may be able to limit viral replication by innate immune mechanisms or cellular immunity is dominant in mediating viral clearance 17,18 .…”
Section: Discussionsupporting
confidence: 92%
“…In our comparison to commercially available IVD tests, we classified fewer samples as false negative using our MultiCoV-Ab assay. For 10% of all infected samples, we could not detect a SARS-CoV-2 specific immune response, which is in line with previous findings 3,15,16 . Those non-responders may be able to limit viral replication by innate immune mechanisms or cellular immunity is dominant in mediating viral clearance 17,18 .…”
Section: Discussionsupporting
confidence: 92%
“…IgA and IgM seroreversion was estimated between days 71 and 49, respectively 8 , but IgA has also been found to remain detectable 6 months post infection and to be less affected by the decay than IgM 9,10 . Several studies have observed relatively stable levels of IgG to the spike (S) protein after three 11,6 , four 12,13 and six to eight months 2,9,14-16 . However, others reported that IgG only lasted around 3-4 months PSO 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Results of serological testing in a low prevalence situation need to be interpreted with caution, as low-level cross-reactivity has been observed for most currently available assays (6). A good practice can be to use combined assay results, counting only samples that had antibody reactivity to two or three of the SARS-CoV-2 antigens as positives(7). By using this criterion, and the high stringency cut-off defined by ROC analysis including serum samples form persons with recent seasonal coronavirus infections, we trust that our estimates are robust.…”
mentioning
confidence: 99%